TATA KELOLA PERUSAHAAN DAN VARIABILITAS LABA - Ikka Tiaraintan Hariyanto; Novrys Suhardianto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
This research aims to examine the influence of firm size, leverage, and corporate governance on earnings variability. We relate the earnings variability with the hypotheses of positive accounting theory and governance mechanism in Indonesia to identify factors that influence earnings variability. Using purposive sampling, we got 628 observations of Indonesian public firms during 2012 until 2014. This research uses common and fixed effect regression model to analyse the data. The results of this analysis show that the big firms have higher profit variability due to higher business and political risks. However, this finding applies only to samples with weak governance. Moreover, the greater the debt the company has, the greater the level of profit variability. This is due to the company's incentives to avoid breaching the debt contract, such as maintaining debt to equity ratio, working capital, or shareholder equity, by adopting aggressive accounting policies. Lastly, the CG mechanism does not affect the variability in earnings, indicating the lack of effective corporate governance in Indonesia. The CG mechanism in Indonesia has not generally been able to influence financial reporting behavior and capital market regulators need to take action to improve the effectiveness of corporate governance in Indonesia.